2018
DOI: 10.1051/0004-6361/201832985
|View full text |Cite
|
Sign up to set email alerts
|

The effects of magnetic field strength on the properties of wind generated from hot accretion flow

Abstract: Context. Observations indicate that wind can be generated in hot accretion flow. By performing numerical simulations, Yuan et al. studied the detailed properties of wind generated from weakly magnetized accretion flow. However, properties of wind generated from strongly magnetized hot accretion flow have not been studied. Aims. In this paper, we study the properties of wind generated from both weakly and strongly magnetized accretion flow. We focus on how the magnetic field strength affects the wind properties… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…We used simple onedimensional self-similar solutions for the density and magnetic field strength in the hot accretion flows model, while it is unclear whether this is valid or not. Studies of two dimensional solutions of hot accretion flows showed a breakdown of spherical symmetry (e.g., Mosallanezhad et al 2016;Bu & Mosallanezhad 2018), though the behavior of physical parameters measured close to the jet axis is poorly constrained yet. We assumed ≈ 130 rad/m 2 for the contribution of the diffuse gas in M87 outside the Bondi radius based on the results of RM studies of the large scale jet but this could be uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…We used simple onedimensional self-similar solutions for the density and magnetic field strength in the hot accretion flows model, while it is unclear whether this is valid or not. Studies of two dimensional solutions of hot accretion flows showed a breakdown of spherical symmetry (e.g., Mosallanezhad et al 2016;Bu & Mosallanezhad 2018), though the behavior of physical parameters measured close to the jet axis is poorly constrained yet. We assumed ≈ 130 rad/m 2 for the contribution of the diffuse gas in M87 outside the Bondi radius based on the results of RM studies of the large scale jet but this could be uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…There are also some analytical works that study the wind from accretion disks (e.g. Li & Cao 2009;Xie et al 2008;Bu et al 2009;Bu & Mosallanezhad 2018;Abbassi et al 2010;Chen et al 2012;Li & Begelman 2014;Gu 2015;Cao 2016). The topic of the wind is interesting because it is now widely believed that AGN feedback plays an important role in the evolution of their host galaxies (e.g., Ciotti & Ostriker 2001, 2007Gan et al 2014;Yuan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Equation 2, ∇•T represents angular momentum transfer by the turbulent magnetic field. We assume T only has azimuthal component, see [10,58,88].…”
Section: Basic Mhd Equationsmentioning
confidence: 99%
“…As with previous works (e.g., [58,88,[92][93][94]), we seek the radially self-similar solutions in the following forms:…”
Section: Basic Mhd Equationsmentioning
confidence: 99%
See 1 more Smart Citation